Adaptation and Response in Drylands: A Dryland Research Agenda and Campaign Strategy - Andrew F. Feldman; Sasha C. Reed; Konrad Wessels; Dennis Ojima; David J. P. Moore; William K. Smith; Niall P. Hanan; Cibele Amaral; Flurin Babst; Joel A. Biederman; Marcy Litvak; Natasha MacBean; et al. (Global Change Biology, 2026)
Dryland ecosystems cover 41% of Earth's land surfaces, account for 44% of cultivated lands and 60% of food sources, and make large contributions to the global water and carbon cycles. However, these ecosystems are experiencing unprecedented extremes including heatwaves, floods, and droughts as well as hotter temperatures and often declining water resource availability. These ecosystems are some of the most challenging to monitor given their high temporal variability with rapid response to their environment as well as vast spatial variability with intermixing of different plant species and life forms amongst bare soil coverage. The Adaptation and Response in Drylands (ARID) campaign was selected by National Aeronautics and Space Administration (NASA) as a scoping study to develop a research agenda for a dryland field campaign. Here, we detail our ARID science research agenda and implementation plan that were developed based on an extensive community engagement effort in over 160 events with over a thousand scientists, land managers, and Tribal communities between 2023 and 2024. The selected science themes cover drought and climate variability, ecosystem structure, function, and biodiversity, carbon cycle interannual variability and trends, and social ecological systems (land management and adaptation). We then detail our remote sensing, modeling, and field‐based strategies to capture high temporal and high spatial resolution processes. Finally, our implementation strategy is presented which includes focus area selections in a core intensive western U.S. domain and distributed international domains. This strategy includes our overarching guiding principles of using multi‐temporal airborne acquisitions and super sites as well as enhancing land management in co‐development with end‐user partners. While originally developed for NASA, our ARID report creates a blueprint for any future dryland field campaign, at any scale, that can be implemented widely for foundational and applied science objectives.

Global Assessment of Environmental and Plant‐Trait Influences on Root: Shoot Biomass Ratios - Ruijie Ding; Rodolfo L. B. Nóbrega; Iain Colin Prentice (Global Change Biology, 2025)
The distribution of assimilated carbon (C) among roots, stems, and leaves is a central process in terrestrial ecosystem dynamics. Yet the biomass allocation schemes used in current global vegetation and land surface models pre‐date the existence of large plant‐trait data sets and remain largely untested. Here we formulate hypotheses on the controls of root: shoot biomass ratios (R:S), based on eco‐evolutionary optimality principles, and assess them quantitatively by analysing data on nearly 30,000 observations of R:S. We analysed global R:S patterns using multiple linear regression models for woody and herbaceous species separately, considering as candidate predictors growing‐season mean temperature ( T g ), gross primary production (GPP), a measure of root‐zone water capacity (RZ WC ), soil pH, sand content, aridity index (AI), and plant traits: vegetation height (H), leaf thickness (LT), leaf dry matter content (LDMC), specific leaf area (SLA), specific root length (SRL), and rooting depth (RRD). R:S was systematically greater in herbaceous plants. R:S decreased with T g , GPP, and height but increased with sand content, RRD, and LDMC in both woody and herbaceous plants. However, AI and leaf thickness had opposing effects on R:S. RZ WC and SLA were important in woody plants, while pH and SRL played a larger role in herbaceous plants. The models explained 13% (woody) and 31% (herbaceous) of R:S variation. The lower explanatory power for woody plants is likely influenced by unmeasured variations in (for example) forest age and canopy position. These empirical findings provide a step towards a quantitative theory of plant C allocation responses to resource availability and an improved C allocation scheme for ecosystem models.

Clarifying the role of the resist–accept–direct framework in supporting resource management planning processes - Gregor W. Schuurman; Wylie Carr; Cat Hawkins Hoffman; David J. Lawrence; Brian W. Miller; Erik A. Beever; Jean Brennan; Katherine R. Clifford; Scott Covington; Shelley D. Crausbay; Amanda E. Cravens; John Gross; et al. (Conservation Biology, 2025)

Seagrass wasting disease prevalence and lesion area increase with invertebrate grazing across the northeastern Pacific - Lillian R. Aoki; Carmen J. Ritter; Deanna S. Beatty; Lia K. Domke; Ginny L. Eckert; Olivia J. Graham; Carla P. Gomes; Collin Gross; Timothy L. Hawthorne; Eliza Heery; Margot Hessing‐Lewis; Kevin Hovel; et al. (Ecology, 2025)
Disease is a key driver of community and ecosystem structure, especially when it strikes foundation species. In the widespread marine foundation species eelgrass ( Zostera marina ), outbreaks of wasting disease have caused large‐scale meadow collapse in the past, and the causative pathogen, Labyrinthula zosterae , is commonly found in meadows globally. Research to date has mainly focused on abiotic environmental drivers of seagrass wasting disease, but there is strong evidence from other systems that biotic interactions such as herbivory can facilitate plant diseases. How biotic interactions influence seagrass wasting disease in the field is unknown but is potentially important for understanding dynamics of this globally valuable and declining habitat. Here, we investigated links between epifaunal grazers and seagrass wasting disease using a latitudinal field study across 32 eelgrass meadows distributed from southeastern Alaska to southern California. From 2019 to 2021, we conducted annual surveys to assess eelgrass shoot density, morphology, epifauna community, and the prevalence and lesion area of wasting disease infections. We integrated field data with satellite measurements of sea surface temperature and used structural equation modeling to test the magnitude and direction of possible drivers of wasting disease. Our results show that grazing by small invertebrates was associated with a 29% increase in prevalence of wasting disease infections and that both the prevalence and lesion area of disease increased with total epifauna abundances. Furthermore, these relationships differed among taxa; disease levels increased with snail ( Lacuna spp.) and idoteid isopod abundances but were not related to abundance of ampithoid amphipods. This field study across 23° of latitude suggests a prominent role for invertebrate consumers in facilitating disease outbreaks with potentially large impacts on coastal seagrass ecosystems.

Diet and Chronic Disease Research in the Women’s Health Initiative - Ross L. Prentice (Journal of the Academy of Nutrition and Dietetics, 2024)

Association of youth climate change worry with present and past mental health symptoms: a longitudinal population-based study - Francis Vergunst; Caitlin M. Prentice; Massimiliano Orri; Helen L. Berry; Vincent Paquin; Frank Vitaro; Richard Tremblay; Sylvana M. Côté; Marie-Claude Geoffroy (Climatic Change, 2024)
Young people are worried about climate change but the association with current and past mental health symptoms is rarely examined in longitudinal population-based samples. Drawing on a population-based birth cohort from the Canadian province of Quebec ( n = 1325), this study used a cross-over design to (1) test the association between climate change worry at age 23-years and concurrent mental health symptoms assessed on standardised instruments, and (2) test the association between adolescent (15 and 17 years) symptoms of anxiety, depression, inattention-hyperactivity, and aggression-opposition and climate worry at age 23-years. Participant sex, cognitive ability, socioeconomic status, and parental mental health were adjusted for. Descriptive statistics showed that most participants were worried about climate change: 190 (14.3%) were extremely worried, 383 (28.9%) were very worried, 553 (41.7%) were somewhat worried, and 199 (15.0%) were not at all worried. In analysis 1, worry about climate change was associated with significantly higher concurrent anxiety, depression, and self-harm symptoms, even after adjustment for adolescent symptoms. In analysis 2, anxious adolescents were significantly more likely to be extremely worried about climate change six years later (RRR = 1.51, 95%CI = 1.10–2.07), while aggressive-oppositional adolescents were significantly less likely to be somewhat worried (RRR = 0.79, 95%CI = 0.63–0.0.99), very worried (RRR = 0.61, 95%CI = 0.48–0.78), or extremely worried (RRR = 0.51, 95%CI = 0.37–0.72). Taken together, participants who were worried about climate change had more concurrent mental health symptoms but were also more likely to have prior symptoms. Adolescents with higher anxiety were more likely to worry about climate change in early adulthood, while those with higher aggression-opposition were less likely to worry. Future studies should track climate worry longitudinally alongside symptoms using prospective follow-up studies.

Disease surveillance by artificial intelligence links eelgrass wasting disease to ocean warming across latitudes - Lillian R. Aoki; Brendan Rappazzo; Deanna S. Beatty; Lia K. Domke; Ginny L. Eckert; Morgan E. Eisenlord; Olivia J. Graham; Leah Harper; Timothy L. Hawthorne; Margot Hessing‐Lewis; Kevin A. Hovel; Zachary L. Monteith; et al. (Limnology and Oceanography, 2022)
Ocean warming endangers coastal ecosystems through increased risk of infectious disease, yet detection, surveillance, and forecasting of marine diseases remain limited. Eelgrass ( Zostera marina ) meadows provide essential coastal habitat and are vulnerable to a temperature‐sensitive wasting disease caused by the protist Labyrinthula zosterae . We assessed wasting disease sensitivity to warming temperatures across a 3500 km study range by combining long‐term satellite remote sensing of ocean temperature with field surveys from 32 meadows along the Pacific coast of North America in 2019. Between 11% and 99% of plants were infected in individual meadows, with up to 35% of plant tissue damaged. Disease prevalence was 3× higher in locations with warm temperature anomalies in summer, indicating that the risk of wasting disease will increase with climate warming throughout the geographic range for eelgrass. Large‐scale surveys were made possible for the first time by the Eelgrass Lesion Image Segmentation Application, an artificial intelligence (AI) system that quantifies eelgrass wasting disease 5000× faster and with comparable accuracy to a human expert. This study highlights the value of AI in marine biological observing specifically for detecting widespread climate‐driven disease outbreaks.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Targeting a coatomer protein complex-I gene via RNA interference results in effective lethality in the pollen beetle Brassicogethes aeneus - Jonathan Willow; Silva Sulg; Clauvis Nji Tizi Taning; Ana Isabel Silva; Olivier Christiaens; Riina Kaasik; Katterinne Prentice; Gabor L. Lövei; Guy Smagghe; Eve Veromann (Journal of Pest Science, 2021)
The pollen beetle Brassicogethes aeneus is a serious pest of oilseed rape ( Brassica napus ) in Europe. Management of this pest has grown difficult due to B. aeneus ’s development of resistance to pyrethroid insecticides, as well as the pressure to establish control strategies that minimise the impact on nontarget organisms. RNA interference represents a nucleotide sequence-based, and thus potentially species-specific, approach to agricultural pest control. The present study examined the efficacy of targeting the coatomer gene coatomer subunit alpha ( αCOP ), via both microinjection and dietary exposure to exogenous complementary dsRNA, on αCOP -silencing and subsequent mortality in B. aeneus . Beetles injected with dsRNA targeting αCOP (at 0.14 µg/mg) showed 88% and 100% mortality at 6 and 10 days post-injection, respectively; where by the same time after dietary exposure, 43%–89% mortality was observed in the 3 µg dsRNA/µL treatment, though the effect was concentration-dependent. Thus, the effect was significant for both delivery routes. In working towards RNA-based management of B. aeneus , future studies should include αCOP as a target of interest.

Spatial and environmental influences on selection in a clock gene coding trinucleotide repeat in Canada lynx (Lynx canadensis) - Melanie B. Prentice; Jeff Bowman; Dennis L. Murray; Kamal Khidas; Paul J. Wilson (Molecular Ecology, 2020)
Clock genes exhibit substantial control over gene expression and ultimately life‐histories using external cues such as photoperiod, and are thus likely to be critical for adaptation to shifting seasonal conditions and novel environments as species redistribute their ranges under climate change. Coding trinucleotide repeats (cTNRs) are found within several clock genes, and may be interesting targets of selection due to their containment within exonic regions and elevated mutation rates. Here, we conduct inter‐specific characterization of the NR1D1 cTNR between Canada lynx and bobcat, and intra‐specific spatial and environmental association analyses of neutral microsatellites and our functional cTNR marker, to investigate the role of selection on this locus in Canada lynx. We report signatures of divergent selection between lynx and bobcat, with the potential for hybrid‐mediated gene flow in the area of range overlap. We also provide evidence that this locus is under selection across Canada lynx in eastern Canada, with both spatial and environmental variables significantly contributing to the explained variation, after controlling for neutral population structure. These results suggest that cTNRs may play an important role in the generation of functional diversity within some mammal species, and allow for contemporary rates of adaptation in wild populations in response to environmental change. We encourage continued investment into the study of cTNR markers to better understand their broader relevance to the evolution and adaptation of mammals.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Integrating national Red Lists for prioritising conservation actions for European butterflies - Dirk Maes; Rudi Verovnik; Martin Wiemers; Dimitri Brosens; Stoyan Beshkov; Simona Bonelli; Jaroslaw Buszko; Lisette Cantú-Salazar; Louis-Francis Cassar; Sue Collins; Vlad Dincă; Milan Djuric; et al. (Journal of Insect Conservation, 2019)

Global photosynthetic capacity is optimized to the environment - Nicholas G. Smith; Trevor F. Keenan; I. Colin Prentice; Han Wang; Ian J. Wright; Ülo Niinemets; Kristine Y. Crous; Tomas F. Domingues; Rossella Guerrieri; F. Yoko Ishida; Jens Kattge; Eric L. Kruger; et al. (Ecology Letters, 2019)

Trans-ethnic fine-mapping of genetic loci for body mass index in the diverse ancestral populations of the Population Architecture using Genomics and Epidemiology (PAGE) Study reveals evidence for multiple signals at established loci - Lindsay Fernández-Rhodes; Jian Gong; Jeffrey Haessler; Nora Franceschini; Mariaelisa Graff; Katherine K. Nishimura; Yujie Wang; Heather M. Highland; Sachiko Yoneyama; William S. Bush; Robert Goodloe; Marylyn D. Ritchie; et al. (Human Genetics, 2017)

A global meta‐analysis of the relative extent of intraspecific trait variation in plant communities - Andrew Siefert; Cyrille Violle; Loïc Chalmandrier; Cécile H. Albert; Adrien Taudiere; Alex Fajardo; Lonnie W. Aarssen; Christopher Baraloto; Marcos B. Carlucci; Marcus V. Cianciaruso; Vinícius de L. Dantas; Francesco de Bello; et al. (Ecology Letters, 2015)
Recent studies have shown that accounting for intraspecific trait variation ( ITV ) may better address major questions in community ecology. However, a general picture of the relative extent of ITV compared to interspecific trait variation in plant communities is still missing. Here, we conducted a meta‐analysis of the relative extent of ITV within and among plant communities worldwide, using a data set encompassing 629 communities (plots) and 36 functional traits. Overall, ITV accounted for 25% of the total trait variation within communities and 32% of the total trait variation among communities on average. The relative extent of ITV tended to be greater for whole‐plant (e.g. plant height) vs. organ‐level traits and for leaf chemical (e.g. leaf N and P concentration) vs. leaf morphological (e.g. leaf area and thickness) traits. The relative amount of ITV decreased with increasing species richness and spatial extent, but did not vary with plant growth form or climate. These results highlight global patterns in the relative importance of ITV in plant communities, providing practical guidelines for when researchers should include ITV in trait‐based community and ecosystem studies.

Reconstructed Ancestral Enzymes Impose a Fitness Cost upon Modern Bacteria Despite Exhibiting Favourable Biochemical Properties - Joanne K. Hobbs; Erica J. Prentice; Mathieu Groussin; Vickery L. Arcus (Journal of Molecular Evolution, 2015)

HLA class I, KIR, and genome-wide SNP diversity in the RV144 Thai phase 3 HIV vaccine clinical trial - Heather A. Prentice; Philip K. Ehrenberg; Karen M. Baldwin; Aviva Geretz; Charla Andrews; Sorachai Nitayaphan; Supachai Rerks-Ngarm; Jaranit Kaewkungwal; Punnee Pitisuttithum; Robert J. O’Connell; Merlin L. Robb; Jerome H. Kim; et al. (Immunogenetics, 2014)

Meta-analysis of new genome-wide association studies of colorectal cancer risk - Ulrike Peters; Carolyn M. Hutter; Li Hsu; Fredrick R. Schumacher; David V. Conti; Christopher S. Carlson; Christopher K. Edlund; Robert W. Haile; Steven Gallinger; Brent W. Zanke; Mathieu Lemire; Jagadish Rangrej; et al. (Human Genetics, 2012)

TRY – a global database of plant traits - J. KATTGE; S. DÍAZ; S. LAVOREL; I. C. PRENTICE; P. LEADLEY; G. BÖNISCH; E. GARNIER; M. WESTOBY; P. B. REICH; I. J. WRIGHT; J. H. C. CORNELISSEN; C. VIOLLE; et al. (Global Change Biology, 2011)
Plant traits – the morphological, anatomical, physiological, biochemical and phenological characteristics of plants and their organs – determine how primary producers respond to environmental factors, affect other trophic levels, influence ecosystem processes and services and provide a link from species richness to ecosystem functional diversity. Trait data thus represent the raw material for a wide range of research from evolutionary biology, community and functional ecology to biogeography. Here we present the global database initiative named TRY, which has united a wide range of the plant trait research community worldwide and gained an unprecedented buy‐in of trait data: so far 93 trait databases have been contributed. The data repository currently contains almost three million trait entries for 69 000 out of the world's 300 000 plant species, with a focus on 52 groups of traits characterizing the vegetative and regeneration stages of the plant life cycle, including growth, dispersal, establishment and persistence. A first data analysis shows that most plant traits are approximately log‐normally distributed, with widely differing ranges of variation across traits. Most trait variation is between species (interspecific), but significant intraspecific variation is also documented, up to 40% of the overall variation. Plant functional types (PFTs), as commonly used in vegetation models, capture a substantial fraction of the observed variation – but for several traits most variation occurs within PFTs, up to 75% of the overall variation. In the context of vegetation models these traits would better be represented by state variables rather than fixed parameter values. The improved availability of plant trait data in the unified global database is expected to support a paradigm shift from species to trait‐based ecology, offer new opportunities for synthetic plant trait research and enable a more realistic and empirically grounded representation of terrestrial vegetation in Earth system models.

Cohorts and consortia conference: a summary report (Banff, Canada, June 17–19, 2009) - Paolo Boffetta; Graham A. Colditz; John D. Potter; Laurence Kolonel; Paula J. Robson; Reza Malekzadeh; Daniela Seminara; Ellen L. Goode; Keun-Young Yoo; Paul Demers; Richard Gallagher; Ross Prentice; et al. (Cancer Causes & Control, 2011)

Common polymorphic variation in the genetically diverse African insulin gene and its association with size at birth - Clive J. Petry; Pura Rayco-Solon; Anthony J. C. Fulford; John D. H. Stead; Dianne L. Wingate; Ken K. Ong; Giorgio Sirugo; Andrew M. Prentice; David B. Dunger (Human Genetics, 2009)

Evaluation of the terrestrial carbon cycle, future plant geography and climate‐carbon cycle feedbacks using five Dynamic Global Vegetation Models (DGVMs) - S. SITCH; C. HUNTINGFORD; N. GEDNEY; P. E. LEVY; M. LOMAS; S. L. PIAO; R. BETTS; P. CIAIS; P. COX; P. FRIEDLINGSTEIN; C. D. JONES; I. C. PRENTICE; et al. (Global Change Biology, 2008)
This study tests the ability of five Dynamic Global Vegetation Models (DGVMs), forced with observed climatology and atmospheric CO 2 , to model the contemporary global carbon cycle. The DGVMs are also coupled to a fast ‘climate analogue model’, based on the Hadley Centre General Circulation Model (GCM), and run into the future for four Special Report Emission Scenarios (SRES): A1FI, A2, B1, B2. Results show that all DGVMs are consistent with the contemporary global land carbon budget. Under the more extreme projections of future environmental change, the responses of the DGVMs diverge markedly. In particular, large uncertainties are associated with the response of tropical vegetation to drought and boreal ecosystems to elevated temperatures and changing soil moisture status. The DGVMs show more divergence in their response to regional changes in climate than to increases in atmospheric CO 2 content. All models simulate a release of land carbon in response to climate, when physiological effects of elevated atmospheric CO 2 on plant production are not considered, implying a positive terrestrial climate‐carbon cycle feedback. All DGVMs simulate a reduction in global net primary production (NPP) and a decrease in soil residence time in the tropics and extra‐tropics in response to future climate. When both counteracting effects of climate and atmospheric CO 2 on ecosystem function are considered, all the DGVMs simulate cumulative net land carbon uptake over the 21st century for the four SRES emission scenarios. However, for the most extreme A1FI emissions scenario, three out of five DGVMs simulate an annual net source of CO 2 from the land to the atmosphere in the final decades of the 21st century. For this scenario, cumulative land uptake differs by 494 Pg C among DGVMs over the 21st century. This uncertainty is equivalent to over 50 years of anthropogenic emissions at current levels.

Changes in fire regimes since the Last Glacial Maximum: an assessment based on a global synthesis and analysis of charcoal data - M. J. Power; J. Marlon; N. Ortiz; P. J. Bartlein; S. P. Harrison; F. E. Mayle; A. Ballouche; R. H. W. Bradshaw; C. Carcaillet; C. Cordova; S. Mooney; P. I. Moreno; et al. (Climate Dynamics, 2008)

Chloroplast DNA variation in the European herb Silene dioica (red campion): postglacial migration and interspecific introgression - Honor C. Prentice; J. U. Malm; L. Hathaway (Plant Systematics and Evolution, 2008)

Acute stress response of Kootenai River white sturgeon Acipenser transmontanus Richardson reflected in peritoneal fluid and blood plasma - M. D. Zuccarelli; M. Kusakabe; I. Nakamura; E. F. Prentice; G. Young; R. L. Ingermann (Journal of Fish Biology, 2008)
To evaluate whether stress‐response indicators in blood plasma (BP) are similarly reflected in the peritoneal fluid (PF) white sturgeon Acipenser transmontanus were stressed by a 30 min air exposure and pH, PCO 2 , osmolality, cortisol, glucose and lactate levels measured. Changes in certain stress indicators in the BP (pH, PCO 2 , osmolality and glucose) also occurred in the PF, while stressor‐induced changes in cortisol and lactate were restricted to the BP. Data suggest that PF is a modified ultrafiltrate of the blood and potentially a useful indicator of animal stress.

Antarctic environments and resources: a geographical perspective. J.D. Hansom and J.E. Gordon. Publisher: Addison Wesley Longman, London 1998 (402 pp) £21.99 ISBN 0‐582‐08127‐0 - Mike L. Prentice (Journal of Quaternary Science, 2000)

Palaeovegetation of China: a pollen data‐based synthesis for the mid‐Holocene and last glacial maximum - G. Yu; X. Chen; J. Ni; R. Cheddadi; J. Guiot; H. Han; S. P. Harrison; C. Huang; M. Ke; Z. Kong; S. Li; W. Li; et al. (Journal of Biogeography, 2000)
Pollen data from China for 6000 and 18,000 14 C yr bp were compiled and used to reconstruct palaeovegetation patterns, using complete taxon lists where possible and a biomization procedure that entailed the assignment of 645 pollen taxa to plant functional types. A set of 658 modern pollen samples spanning all biomes and regions provided a comprehensive test for this procedure and showed convincing agreement between reconstructed biomes and present natural vegetation types, both geographically and in terms of the elevation gradients in mountain regions of north‐eastern and south‐western China. The 6000 14 C yr bp map confirms earlier studies in showing that the forest biomes in eastern China were systematically shifted northwards and extended westwards during the mid‐Holocene. Tropical rain forest occurred on mainland China at sites characterized today by either tropical seasonal or broadleaved evergreen/warm mixed forest. Broadleaved evergreen/warm mixed forest occurred further north than today, and at higher elevation sites within the modern latitudinal range of this biome. The northern limit of temperate deciduous forest was shifted c. 800 km north relative to today. The 18,000 14 C yr bp map shows that steppe and even desert vegetation extended to the modern coast of eastern China at the last glacial maximum, replacing today’s temperate deciduous forest. Tropical forests were excluded from China and broadleaved evergreen/warm mixed forest had retreated to tropical latitudes, while taiga extended southwards to c . 43°N.

The Effect of Hormones on the Expression of Five Isoforms of UDP-Glucuronosyltransferase in Primary Cultures of Rat Hepatocytes - Van Q. Li; David A. Prentice; Monique L. Howard; Maurice L. Mashford; Paul V. Desmond (Pharmaceutical Research, 1999)

Coupling dynamic models of climate and vegetation - JONATHAN A. FOLEY; SAMUEL LEVIS; COLIN I. PRENTICE; DAVID POLLARD; STARLEY L. THOMPSON (Global Change Biology, 1998)

Coupling dynamic models of climate and vegetation - Jonathan A. Foley; Samuel Levis; I. Colin Prentice; David Pollard; Starley L. Thompson (Global Change Biology, 1998)
Numerous studies have underscored the importance of terrestrial ecosystems as an integral component of the Earth's climate system. This realization has already led to efforts to link simple equilibrium vegetation models with Atmospheric General Circulation Models through iterative coupling procedures. While these linked models have pointed to several possible climate–vegetation feedback mechanisms, they have been limited by two shortcomings: (i) they only consider the equilibrium response of vegetation to shifting climatic conditions and therefore cannot be used to explore transient interactions between climate and vegetation; and (ii) the representations of vegetation processes and land‐atmosphere exchange processes are still treated by two separate models and, as a result, may contain physical or ecological inconsistencies. Here we present, as a proof concept, a more tightly integrated framework for simulating global climate and vegetation interactions. The prototype coupled model consists of the GENESIS (version 2) Atmospheric General Circulation Model and the IBIS (version 1) Dynamic Global Vegetation Model. The two models are directly coupled through a common treatment of land surface and ecophysiological processes, which is used to calculate the energy, water, carbon, and momentum fluxes between vegetation, soils, and the atmosphere. On one side of the interface, GENESIS simulates the physics and general circulation of the atmosphere. On the other side, IBIS predicts transient changes in the vegetation structure through changes in the carbon balance and competition among plants within terrestrial ecosystems. As an initial test of this modelling framework, we perform a 30 year simulation in which the coupled model is supplied with modern CO 2 concentrations, observed ocean temperatures, and modern insolation. In this exploratory study, we run the GENESIS atmospheric model at relatively coarse horizontal resolution (4.5° latitude by 7.5° longitude) and IBIS at moderate resolution (2° latitude by 2° longitude). We initialize the models with globally uniform climatic conditions and the modern distribution of potential vegetation cover. While the simulation does not fully reach equilibrium by the end of the run, several general features of the coupled model behaviour emerge. We compare the results of the coupled model against the observed patterns of modern climate. The model correctly simulates the basic zonal distribution of temperature and precipitation, but several important regional biases remain. In particular, there is a significant warm bias in the high northern latitudes, and cooler than observed conditions over the Himalayas, central South America, and north‐central Africa. In terms of precipitation, the model simulates drier than observed conditions in much of South America, equatorial Africa and Indonesia, with wetter than observed conditions in northern Africa and China. Comparing the model results against observed patterns of vegetation cover shows that the general placement of forests and grasslands is roughly captured by the model. In addition, the model simulates a roughly correct separation of evergreen and deciduous forests in the tropical, temperate and boreal zones. However, the general patterns of global vegetation cover are only approximately correct: there are still significant regional biases in the simulation. In particular, forest cover is not simulated correctly in large portions of central Canada and southern South America, and grasslands extend too far into northern Africa. These preliminary results demonstrate the feasibility of coupling climate models with fully dynamic representations of the terrestrial biosphere. Continued development of fully coupled climate‐vegetation models will facilitate the exploration of a broad range of global change issues, including the potential role of vegetation feedbacks within the climate system, and the impact of climate variability and transient climate change on the terrestrial biosphere.